Swearing as a Communicative Resource in Film Dialogue: A Pragmatic Analysis of The Intern (2015) - Nur'aini, Nilam; Romadlon, Farid Noor; Rasheed, Abdul (New Language Dimensions, 2025)
Swearing, often stigmatized as impolite, fulfills diverse pragmatic functions in everyday and mediated discourse. Despite increasing scholarly attention, limited research has examined how swearing is employed in cross-generational workplace comedies. This study investigates the lexical types and pragmatic functions of swear words in The Intern (2015). Adopting a qualitative descriptive approach, the study analyzed all utterances containing swearing in the film. Data were collected through repeated viewing, transcription, and verification with subtitles to ensure accuracy. The lexical classification followed Hughes’ (2006) typology, while functional analysis was guided by Andersson and Trudgill’s framework, adapted to the filmic context. Thirty-eight instances of swearing were identified across four lexical categories: religious terms (e.g., “oh my God”), sexual expressions (e.g., “ass,” “fucking”), animal references (e.g., “bitch”), and mental-state terms (e.g., “crazy,” “maniac”). These fulfilled four pragmatic functions: expletive (spontaneous emotion), abusive (other-directed offence), humorous (affiliative purposes), and auxiliary (intensification). Jules Ostin, the female protagonist, produced the highest frequency, with expletive swearing predominating. The findings demonstrate that swearing in The Intern is a versatile pragmatic resource that indexes stance, emotion, and relational alignment, rather than merely signaling impoliteness. The study extends understanding of cinematic discourse and highlights pedagogical implications for raising EFL learners’ sociolinguistic awareness of taboo language. Future research could examine genre and cross-cultural variation to illuminate the contextual shaping of swearing practices further.